Tensile and Flexural Properties of 3D-Printed Polylactic Acid/Continuous Carbon Fiber Composite - Ali Khalili; Abdolvahed Kami; Vahid Abedini (Mechanics of Advanced Composite Structures)
Fused deposition modeling is one of the most common methods of additive manufacturing that has enabled the 3D printing of composites. Compared with traditional procedures, this method reduces part cost and production time. This paper investigated the effects of layer height, print speed, and nozzle temperature on the tensile and flexural characteristics of polylactic acid/continuous carbon fiber (PLA/CCF) composite. Two predicting models were developed based on the mechanical tests' data to estimate composite specimens' tensile and flexural strength. These models were used in a two-objective optimization procedure to obtain the composite's highest tensile and flexural strength. The optimum layer thickness, print speed, and nozzle temperature values were 0.3 mm, 4 mm/s, and 200°C, respectively. Adjusting the optimal values of the study parameters increased tensile and flexural strength by 77 and 27.5 percent, respectively, over the unreinforced sample. Furthermore, the fracture section of the composite was examined by scanning electron microscopy (SEM). The SEM images showed that the printing parameters influenced fiber impregnation, which in turn affected the sample's strength. Finally, two composite samples were successfully 3D printed with higher complexity using the optimized values of the studied parameters.